Les géographes français et les États-Unis, XXe siècle - Marielle Wastable (Amnis)
This article presents the exchanges, transfers and go-betweens that influenced the twentieth Century French geographers' discourses on the United States. During some periods of time, they show interest for this country, but at others periods, they tend to distance themselves from it. This echoes the evolution of the French-American relationships as well as the the way this territory is apprehended by French intellectuals.